IBN Haldun's Historical Philosophy (1332-1406) - Juraev, Narzulla (International Journal of Psychosocial Rehabilitation, 2020)
One of the thinkers Abdurakhman Mukhammad Ibn Khaldun, who seriously developed the Eastern philosophical thinking, enriched it with his scientific views and developed a philosophical approach to history. He developed the methodology of historical philosophy. He laid theoretical foundations for researching the past. Ibn Khaldun's philosophy of history is a great philosophy that combines religious and secular philosophical sciences with the categories of history and sociology, cultural studies, human studies, aesthetics and logic, reason and thinking, character and morality. The article examines his views on the philosophy of history.